2000
DOI: 10.4049/jimmunol.164.10.5215
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Expression of the gp49B Inhibitory Receptor on NK Cells

Abstract: Murine NK cells express inhibitory receptors belonging to the C-type lectin-like (Ly-49, CD94/NKG2) and Ig superfamily-related (gp49) receptors. The murine gp49B receptor displays structural homology with human killer inhibitory receptors, and was previously identified to be a receptor on mast cells and activated NK cells. The gp49B receptor is highly related to gp49A, a receptor with unknown function. In this study, using a novel mAb produced against soluble gp49B molecules that cross-reacts with gp49A, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…These considerations demonstrate the necessity of additional experimental work following initial microarray-based screening for relevant genes. Our finding of an antiproliferative and also toxic effect of GP49B was in good agreement with previous work, showing the inhibitory action of this Ig superfamily- (Wang et al, 2000). Our results suggest the existence of a receptor-mediated inhibitory pathway in pro B-cells that counteracts the IL-3 mitogenic signal.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These considerations demonstrate the necessity of additional experimental work following initial microarray-based screening for relevant genes. Our finding of an antiproliferative and also toxic effect of GP49B was in good agreement with previous work, showing the inhibitory action of this Ig superfamily- (Wang et al, 2000). Our results suggest the existence of a receptor-mediated inhibitory pathway in pro B-cells that counteracts the IL-3 mitogenic signal.…”
Section: Discussionsupporting
confidence: 82%
“…Only paclitaxel did not cause an induction of known p53 target genes. An inhibitory function had also been described previously for the glycoprotein GP49B (Wang et al, 2000) that we identified as induced in the camptothecin, cisplatin and paclitaxel responses. Induction of a murine homologue of the inhibitory protein tob (Matsuda et al, 1996) was observed in the camptothecin, cisplatin and methotrexate responses, further confirming the hypothesis that pathway intersections of upregulated transcripts should be enriched for anti-proliferative genes.…”
Section: Gene Expression Analysis By Cdna Microarraysmentioning
confidence: 99%
“…We examined the surface expression of gp49A and gp49B on BMDC and splenic CD11c 1 DC either from B6 or gp49B À/À mice as well as on the BMDC after stimulation with LPS or addition of OVA by flow cytometry with mAb H1.1, which recognizes a common epitope on gp49A and gp49B [35]. As shown in Fig.…”
Section: Bmdc and Splenic DC Express Gp49bmentioning
confidence: 99%
“…Colligation of gp49B with the highaffinity receptor for IgE or the type I FcgR by antibodies inhibits degranulation of mast cells or production of TNF-a by macrophages, respectively [29,34]. Recently, it was reported that gp49B expression can be induced on activated T cells and NK cells stimulated by IL-2, or viral or bacterial infection, and that it regulates IFN-g production and NK cell-mediated cell lysis [35,36]. In in vivo studies, gp49B-deficient (gp49B À/À ) mice exhibited increased severity of passive and active cutaneous anaphylaxis [26].…”
mentioning
confidence: 99%
“…gp49B has been shown to bind to the integrin a v and b 3 (a v b 3 ), which is expressed on a variety of cells including activated T cells, and this interaction inhibits IgE-dependent degranulation of mast cells (30)(31)(32). Other studies showed that gp49B is also expressed on activated T cells and NK cells, and regulates IFN-g production (32)(33)(34). However, the function of gp49B on any B cell subset has not been determined.…”
mentioning
confidence: 99%